Gesichter der Gewalt Beiträge aus phänomenologischer Sicht - Staudigl, Michael
The contributions to this volume develop basic patterns for a non-reductive analysis of violence. They focus violence as perspective phenomenon, i.e., as suffered, enacted, or otherwise experienced, and thus undermine essentialist definitions of this very phenomenon. In applying the phenomenological insight into the lived intertwining of embodied meaning and objective orders, this book traces the many faces of violence in both their specific traits as well as their relational constitution.